Application of the Knowledge Management Assessment Tool – KMAT to systematize Knowledge Management - Muniz, Emerson Cleister Lima; Nascimento, Heloisa Fernandes do (International Congress of Knowledge and Innovation - Ciki, 2023)
Knowledge Management Practices - KM are essential to the competitiveness of companies, being essential, before their application, the analysis of their maturity regarding KM. Thus, this research evaluates the level of Knowledge Management in a company to help the KM systematization in it via a case study preceded by an integrative review. To this end, the Knowledge Management Assessment Tool – KMAT was selected, adapted and applied in the company, obtaining as main points the discovery of the company's maturity level and which categories based on the KMAT contribute or not to the identified level. With this, practical proposals for KM systematization were proposed, aiming to help the company to improve its level and adopt other KM tools in its day-to-day.